To find the slope and the y-intercept of the equation \( 9 + \frac{27}{2}x = -\frac{3}{2}y \), we first need to rearrange this equation into the slope-intercept form, which is \( y = mx + b \), where \( m \) is the slope and \( b \) is the y-intercept.
-
Start by isolating \( y \): \[ 9 + \frac{27}{2}x = -\frac{3}{2}y \]
-
To move \( -\frac{3}{2}y \) to the left side, we'll multiply both sides by \(-1\) to make the \( y \) term positive: \[ -9 - \frac{27}{2}x = \frac{3}{2}y \]
-
Now, we can solve for \( y \) by multiplying both sides by \( \frac{2}{3} \) to isolate \( y \): \[ y = -\frac{2}{3}(-9) - \frac{2}{3}\left(\frac{27}{2}x\right) \]
-
Simplifying this: \[ y = 6 - 9x \]
Now we have the equation in the form \( y = mx + b \):
- The slope \( m = -9 \)
- The y-intercept \( b = 6 \)
The y-intercept can be represented as an ordered pair \( (0, b) \):
- Y-intercept: \( (0, 6) \)
Thus, the final answers are:
- Slope: \( -9 \)
- Y-intercept: \( (0, 6) \)